The bfg - Dahl, Roald; Blake, Quentin (Puffin London, 2016)
The well-loved story of a big friendly giant who spirits a child out of bed to the land of the child-eating giants. Every night, when the world is sleeping, big gruesome giants guzzle up whoppsy-whiffling human beans. And there's only one giant who can stop them, the BFG. He's the kindest giant there is and, with his friend Sophie in his top pocket, he sets out to rid the world of the Bloodbottler, the Fleshlumpeater and all their rotsome friends forever